Nanotechnology and food processing: between innovations and consumer safety. Issue 5 (3rd September 2019) - Adeyeye, Samuel Ayofemi Olalekan; Fayemi, Olanrewaju Emmanuel
ABSTRACT: This review assessed the use of nanotechnologies in food processing and effect of innovations in nanotechnology on food quality and safety. This review delved into applications of nanotechnology in food processing, food packaging and food preservation, nanotechnology and food safety as well as regulation of nanotechnologies to ensure food safety. Nanotechnology usefulness in food processing, food packaging, food monitoring, production of functional foods, development of foods capable of modifying their colour, flavour, or nutritional properties according to a person's dietary needs as well as production of stronger flavourings, colourings, and nutritional food additives cannot be quantified. Lowering the costs of food additive ingredients and increasing the shelf life of food products could also be achieved using nanotechnology. Smart packaging could be used to optimize product shelf-life using nanotechnologies and such packaging systems would be able to repair small holes/tears, respond to environmental conditions such as temperature and moisture changes, and alert the customer if the food is contaminated. Another potential area of application of nanotechnology is in the development of food analytical methods for the detection of tiny amounts of chemical contaminants, virus or bacteria in food system. However, there is a need for regulatory systems capable of managing any risks associated with nanofoods and the use of nanotechnologies in food processing and product development to prevent future catastrophe that could result from the use of nanotechnologies in food processing.